2009
DOI: 10.1159/000212057
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Hamartoma of the Liver: A Benign Tumor with Deceptive Prognosis in the Perinatal Period

Abstract: This article reports a case of perinatal mesenchymal hepatic hamartoma and reviews the literature on the subject. A fetus presented with polyhydramnios and a large multiloculated cystic abdominal mass at 33 weeks of gestation. The ultrasound appearance was most consistent with a mesenteric cyst. Prenatal drainage was considered, due to the size of the lesion. However, a conservative management was opted for. A female infant was born at 35 weeks by classical cesarean section. The immediate postnatal period was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 62 publications
1
11
0
2
Order By: Relevance
“…The ultrasonographic appearance of the lesion was confusing because it did not resemble anything we had seen in the past 20 years. However, the findings were similar to multicystic lesions described for liver hamartoma in human medicine [2,4-6]. In our case, it was not clear initially whether the dilated vessels were blood vessels or bile ducts.…”
Section: Case Presentationsupporting
confidence: 84%
“…The ultrasonographic appearance of the lesion was confusing because it did not resemble anything we had seen in the past 20 years. However, the findings were similar to multicystic lesions described for liver hamartoma in human medicine [2,4-6]. In our case, it was not clear initially whether the dilated vessels were blood vessels or bile ducts.…”
Section: Case Presentationsupporting
confidence: 84%
“…Table 2 shows a comparison of outcomes of reported cases. Of the eight cases found in the literature, there were two fetal demises, one neonatal death, four postnatal surgically resections (two immediately postnatal, one at 3 months and one at 11 months of age), and one had serial postnatal percutaneous decompression with full resolution [3][4][5][6][7][8][9][10]. HMH should always be considered a likely diagnosis in cases of PMD with an associated abdominal mass seen antenatally on ultrasonography.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, when a liver tumor presents as a PMD complication, the parents should be counseled that the fetal prognosis may be poor. Some case reports have described PMD being diagnosed in conjunction with MHL, whereas others describe PMD being detected after an MHL diagnosis . Therefore, obstetricians may need to perform detailed placental ultrasound studies to identify this PMD complication when a fetal liver tumor is found.…”
Section: Discussionmentioning
confidence: 99%